Occurrence of splenic leiomyosarcoma in dog: anatomopathological findings - Moreira, Thaís de Almeida; Lopes, Marcelo Coelho; Santos, Leilane Sousa; de Souza, Rafael Rocha; dos Reis, Júnior Artur; da Rocha Júnior, José Maurício; Bandarra, Márcio de Barros (Medicina Veterinária, 2017)
Leiomyosarcoma is a malignant neoplasm with origin in smooth muscles. It can originate in the vessel wall and interstitium of the spleen smooth muscle, which is considered rare. The objective of this study was to describe clinical and anatomopathological findings of a splenic leiomyosarcoma in an eight-year-old bitch of the Fila breed. This splenic leiomyosarcoma weighed 9.2 kg, and had 30×27×14 cm in dimension, rounded shape, irregular outline, reddish color alternating with pale areas, friable and hemorrhagic tissues, and necrotic center. After conventional histopathological examination, the suspected diagnosis (leiomyosarcoma) was confirmed by histochemical analysis using Masson's trichrome staining (which showed the reactivity of the muscle tissue) and by immunohistochemical analysis, showed positivity for smooth muscle actin, vimentin, and desmin. This study emphasizes the importance of associating histopathological evaluation with histochemical and immunohistochemical techniques for a diagnosis of this neoplasm. The occurrence of leiomyosarcoma reported here denotes the importance of considering it for a differential diagnosis in cases of splenic tumors.